The relationship between the relative velocity lactate turnpoint and the time at VO2max during a constant velocity run to exhaustion in professional endurance runners - Khaledi, N.; Gaeeini, A.; Shahbazi, M. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The minimal running velocity at which the maximal oxygen uptake is elicited during an incremental test to exhaustion (vVO ) has been used to prescribe training. If attaining and sustaining VO during training is an important factor in optimizing its enhancement, it is of interest for exercise physiologists to know which physiological factors predominantly influence the time at which VO can be sustained (TVO2max ). The velocity at the lactate turnpoint (vLTP) is the point in the blood lactate velocity curve associated with a second sudden and sustained increase in blood lactate concentration (Smith and Jones, 2001), and thus gives an indirect indication of the exercise intensity at which lactic acid rapidly accumulates in the muscle. The main aim of this study was to examine the relationship between the vLTP, expression as a percentage of vVO (the relative vLTP), and the TVO2max during a continuous run to exhaustion at vVO . Methods Eleven endurance runners, (mean age (± SD), 24.36; ± 1.1 y) from national teams participated in three test on a treadmill. The time between completion of warm-up and the start of any test was approximately one minute. The first test was a continuous incremental test to determine VO and vVO: the second, a single velocity continuous run at vVO2max to determine Tlim vVO2max , TAVO and TVO2max: and the third to determine vLTP. Metabolic data was collected using an online gas analysis system (k4b2 Cosmed Italy) through the treadmill exercise test periods. Breath-by-breath data was retrograde stationary time-averaged over 15s, 5s, and 60s for tests 1, 2, 3, respectively. Results / Discussion This study has demonstrated that the correlation between the relative vLTP and TVO was not statistically significant. The present results agreed with the results of Midgley et al., (2006). This would account for some of the unexplained variance in TlimvVO not accounted for by the forty percent explained by inter-individual variability in anaerobic capacity. This hypothesis was based on the assumption that the further above the vLTP a runner exercises, the faster blood lactate accumulate, and therefore, the closer the individual`s relative vLTP is to the vVO (Midgley 2006), the slower lactate accumulation will occur. However, although TVO was found to be significantly positively correlated with TlimvVO (r=0.91), a very low insignificant correlation existed between the relative vLTP and TlimvVO (r=0.27). A possible explanation for the contrasting result is that the significant correlation found by Billat et al., (1999) using the results of the Tlim test, but not the second, may be a type of error, which may occur by chance alone once in every 20 comparisons when alpha is accepted as 0.05, Cohen, (1992). Although a lack of statistical power probably influenced this finding. Further research with greater sample sizes is required to substantiate these findings, before final conclusions can be made.